Foreign ownership, financial contraints and financing decisions: evidence from Ghana and China - Gyeke-Dako, Agyapomaa (2011)
Firms playa pivotal role in every economy. Therefore their financial standing should be of great concern to policy-makers, as this may directly affect the overall performance of the economy. Corporate finance literature however suggests that market imperfections resulting from conflicts of interest and informational asymmetries, between different economic agents, limit firms in their ability to finance investment projects. Yet, the extent to which firms are limited depends greatly on their size, ownership, exporting status, risk level and even location. In fact, many studies believe that unless by some policy directives pertaining to a particular country, foreign, exporting, large, less risky and firms in developed regions will under normal circumstances be less financially constrained than their counterparts, domestic, non-exporting, small, more risky and firms in undeveloped regions respectively. For domestic firms, some evidence exists that their financial constraints can be alleviated by the entrance of foreign firms. In this thesis, we try and incorporate as many of these determinants as possible bearing in mind data availability. As a result, in the first part of this study, we address the issue of financial constraints of foreign and domestic firms as well as crowding out effects of domestic firms in Ghana. To the best of our knowledge, no study has attempted to address this particular issue on Ghana. We then move a step higher in the second part of our study by considering this same topic in China but then looking at it using firms with different degrees of foreign ownership. Not only do we do this, but we also carry out regional analysis in this respect. All these are made possible by the quality of dataset that we use in our analyses. Again, to the best of our knowledge, no study has addressed this issue on China in this manner. In the last part of our study, we take a different tum altogether and examine mainly the sensitivities of both long-term debt and short-term debt to cash flow and collateral respectively for globally-engaged firms (foreign-owned and exporting firms) as well as firms in the coastal and non-coastal regions of China. We find very interesting results from these analyses. With regards to evidence on firm financial constraints in Ghana, we find that domestic firms are more financially constrained than foreign firms and that foreign firms' presence has no impact on domestic firms in Ghana. For the results on China, while we find no difference between the financial constraints of purely domestic firms and joint ventures, we find that wholly-foreign owned firms are less financially constrained than purely domestic firms. We however find that the presence of foreign firms help alleviate purely domestic firms from their financial constraints. For the regional analysis, estimates based on this suggest firms in the coastal region are less financially constrained than firms in the non-coastal region. Regarding the sensitivities of both short-term debt and long-term debt to cash flow and collateral, whilst we find that highly globally engaged firms have a higher sensitivity of long-term debt to cash flow than non-globally engaged firms, we find that globally engaged firms' short-term debt have a lower sensitivity to collateral than non-globally engaged firms. As for the regional analysis, our result show that both the short-term debt and long-term debts of firms in the coastal region have a higher sensitivity to collateral and cash flow respectively than the sensitivities of short-term debt and long-term debt to cash flow and collateral of firms in the non-coastal region.